Effects of levosimendan and dobutamine in experimental acute endotoxemia : A preliminary controlled study - Dubin, Arnaldo (2007)
Objective: To test the hypothesis that levosimendan increases systemic and intestinal oxygen delivery (DO2) and prevents intramucosal acidosis in septic shock. Design: Prospective, controlled experimental study. Setting: University-based research laboratory. Subjects: Nineteen anesthetized, mechanically ventilated sheep. Interventions: Endotoxin-treated sheep were randomly assigned to three groups: control (n = 7), dobutamine (10 μg/kg/min, n = 6) and levosimendan (100 μg/kg over 10 min followed by 100 μg/kg/h, n = 6) and treated for 120 min. Measurements and main results: After endotoxin administration, systemic and intestinal DO 2 decreased (24.6 ± 5.2 vs 15.3 ± 3.4 ml/kg/min and 105.0 ± 28.1 vs 55.8 ± 25.9 ml/kg/min, respectively; p < 0.05 for both). Arterial lactate and the intramucosal–arterial PCO2 difference (∆PCO2) increased (1.4 ± 0.3 vs 3.1 ± 1.5 mmHg and 9 ± 6 vs 23 ± 6 mmHg mmol/l, respectively; p < 0.05). Systemic DO 2 was preserved in the dobutamine-treated group (22.3 ± 4.7 vs 26.8 ± 7.0 ml/min/kg, p = NS) but intestinal DO 2 decreased (98.9 ± 0.2 vs 68.0 ± 22.9 ml/min/kg, p < 0.05) and ∆PCO 2 increased (12 ± 5 vs 25 ± 11 mmHg, p < 0.05). The administration of levosimendan prevented declines in systemic and intestinal DO 2 (25.1 ± 3.0 vs 24.0 ± 6.3 ml/min/kg and 111.1 ± 18.0 vs 98.2 ± 23.1 ml/min/kg, p = NS for both) or increases in ∆PCO2 (7 ± 7 vs 10 ± 8, p = NS). Arterial lactate increased in both the dobutamine and levosimendan groups (1.6 ± 0.3 vs 2.5 ± 0.7 and 1.4 ± 0.4 vs. 2.9 ± 1.1 mmol/l, p = NS between groups). Conclusions: Compared with dobutamine, levosimendan increased intestinal blood flow and diminished intramucosal acidosis in this experimental model of sepsis.